Amaranthus hybridus (syn. quitensis) intoxication in cattle in Argentina: Case report - Garcia, Juan Agustin (2023)
Amaranthus spp. is a nephrotoxic plant with unknown toxic principle, affecting production animals worldwide, mainly in South America. The aim of this paper is to describe 5 spontaneous outbreaks of A. hybridus intoxication in beef cattle, where 7 autopsies were performed. Main gross findings were pale diffuse and enlarged kidneys. Microscopically, kidneys were characterized by severe tubular acute to subacute nephrosis, with dilatated tubules showing different degrees of epithelial degeneration and necrosis, and containing intraluminal eosinophilic hyaline casts. Intratubular birefringent crystals, compatible with oxalate, were observed under polarized light in kidneys from 3 autopsies. Positive von Kossa and red alizarin S staining confirmed the intratubular crystals as calcium deposits. This intoxication occurs mainly in stubble paddocks during summer and early autumn. The data from the present study suggests that oxalates were related to nephrotoxicity due to Amaranthus consumption.